2013
DOI: 10.3852/12-249
|View full text |Cite
|
Sign up to set email alerts
|

The sections ofAlternaria: formalizing species-group concepts

Abstract: The systematics of Alternaria and allied genera traditionally has been based on the characteristics of conidia and the sporulation apparatus. This emphasis on morphology in the reconstruction of organismal relationships has resulted in taxonomic uncertainty and flux for a number of taxa in Alternaria and the related genera Stemphylium, Embellisia, Nimbya and Ulocladium. The present study used a molecular phylogenetic approach for systematic resolution and incorporated extensive taxon sampling (n = 176 species)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
234
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(246 citation statements)
references
References 43 publications
9
234
0
3
Order By: Relevance
“…The strain was cultured on potato dextrose agar (PDA; Difco Laboratories, Detroit, Michigan, USA); the colony, conidium morphology and sporulation characteristics of this specie were confirmed according to those described by Simmons (2007), Troncoso-Rojas et al (2005), and Lawrence et al (2013). The colony of A. alternata had a dark olive-green color, felty to wooly texture, with a prominent (2 to 5 mm) white margin and a diameter of over 80 mm after 8 to 10 days of growth.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The strain was cultured on potato dextrose agar (PDA; Difco Laboratories, Detroit, Michigan, USA); the colony, conidium morphology and sporulation characteristics of this specie were confirmed according to those described by Simmons (2007), Troncoso-Rojas et al (2005), and Lawrence et al (2013). The colony of A. alternata had a dark olive-green color, felty to wooly texture, with a prominent (2 to 5 mm) white margin and a diameter of over 80 mm after 8 to 10 days of growth.…”
Section: Plant Materialsmentioning
confidence: 99%
“…All A. burnsii isolates had the same sequence homology on Figure 1. Neighbor-joining tree constructed using Alt a1 gene sequences of Alternaria burnsii isolates from cumin and the reference isolates belonging to different Alternaria section described by Lawrence et al (2013). The numbers at the branch points indicate bootstrap values based on 1000 replicates and F. equiseti comprised 9.5 and 8.71%, respectively while M. phaseolina and A. alternata comprised 2.9 and 2.64% of all isolates.…”
Section: Resultsmentioning
confidence: 99%
“…JQ646388), available for Alt a1 gene of A. burnsii in GenBank. Also, DNA sequencing analysis of Alt a1 gene revealed that A. burnsii was phylogenetically distant to other speciesgroups of Alternaria described by Lawrence et al (2013) (Figure 1). Thus, the identification of A. burnsii isolates was only confirmed based on morphological characteristics described by Simmons (2007).…”
Section: Discussionmentioning
confidence: 99%
“…Son yıllarda Alternaria türleri birbirlerine genetik olarak çok benzeyen farklı tür gruplarını içeren 24 farklı seksiyonda tanımlanmaktadır (Woudenberg et al 2013, Lawrence et al 2013, Lawrence et al 2014. Bu nedenle bu çalışmada bu tür grupları dikkate alınarak sonuçlar sunulmuştur.…”
Section: Sonuçlar Ve Tartişmaunclassified